MANAJEMEN PROSES PEMBELAJARAN DI PONDOK PESANTREN ( Studi Kasus Di Pondok Pesantren Darul Ihsan Samarinda) - Muhammad Zaibi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
The existence and role of boarding schools in the areas of social life of society, required serious attention. Appropriate management and the provision and improvement of human resources in the field of management. The imbalance between the large boarding schools and small schools are so clearly expressed in managing schools. The management a constraint in boarding activities. Management is a real process that starts from planning, organizing, implementing and monitoring conducted to determine or resolve targets by using people and other resources. This research is qualitative research by descriptive analysis. This research is used to dig deeper into the information. With this research model, researchers can formulate the problem in greater detail. So that the researchers used a qualitative approach the an in-depth interview observation.The conclusion from the results of this study are: First, the management programs of Darul Ihsan Samarinda Islamic Boarding School goes well; second, inadequate support facilities at boarding school and the difference with the National Education curriculum schedule is a constraint that encountered in implementing management programs at the Darul Ihsan Samarinda Islamic Boarding School